Laser powder bed fusion of 316L stainless steel with 2 wt.% nanosized SiO2 additives: Powder processing and consolidation - Stylianou, Rafael; Evangelou, Angelos; Loizou, Alexandros; Kim, Donghyuk; Wharton, Julian; Koutsokeras, Loukas E.; Constantinides, Georgios; Delimitis, Andreas; Kyratsi, Theodora (My University, 2023)
Gas atomized 316L stainless steel powder was processed with 2 wt.% of nanosized SiO2 in a planetary ball milling (BM) system to produce feedstock material for laser powder bed fusion (L-PBF). X-ray diffraction (XRD) of powders revealed the development of micro-strains over increasing milling durations and the strain-induced ferrite formation. BM was limited in duration to preserve the austenitic phase and morphological characteristics analyzed by electron microscopy. In turn, 316L-2wt.% SiO2 feedstock powder was consolidated by L-PBF with varied process parameters and scanning strategies, that demonstrated a maximum density of 7.84 g/cm3 and relatively stable microhardness values close to 220 HV. A distinct (110) preferred orientation was observed in XRD pole figures of austenite for deeper melt pools over the building direction, whereas in-plane alignment reflected variations in scanning strategy. Furthermore, electron backscatter diffraction revealed columnar grains accompanied by the suspected depletion of SiO2, while electrochemical behavior displayed consistent characteristics.
Keywords: 316L stainless steel; Ball milling; Crystallographic texture; Melt pools; Selective laser melting; Silica